História e literatura na libertação de Angola: o mito de Ngunga e o engajamento de Pepetela contra o colonialismo - Silva, Alencar Rampelotto da (2018)
The Angola's independence war was one of the most long liberations conflicts of the African continent, having as initial mark anticolonial attacks on Luanda, in 1961. These conflicts their extended, becoming a war which spread throughout most of the territory until one year after the fall of the Portuguese colonial and fascist regime, culminating in the emancipation of Angola in 1975. For the investigation of this historical period it is proposed a qualitative bibliographical analysis on four of the main works of the Angolan novelist, Artur Carlos Mauricio Pestana dos Santos, popularly known as Pepetela (1941), and they are: the historical novels Mayombe (1971) and A Geração da Utopia (1991), the fable of Muana Puó (1969), as well as the main object of this research, the mythological narrative of As Aventuras de Ngunga (1972). In addition, several official documentary sources of the Portuguese government and the African colony are taken into account for completeness and verification of the facts. This study made it possible to compare the discourses of the Angolan liberation movements with emphasis on the Popular Movement for the Liberation of Angola (MPLA) and also on the Portuguese State and its nostalgic idea of the already infamous overseas empire. It is noted that the role played by the Angolan intelligentsia in the guerrilla organization in the face of its contradictions and in the configuration of the bases of the national state of Pan-African character, inspired by the utopian projections with the rise of the so-called Third World, is also outstanding. In relation to the ambition of the intellectuals to build the political and cultural foundations of the new nation, we highlight the dialectical exploration of the question of hybridism, or rather, miscegenation of Angolan society with its tradition of orality and its cyclic cosmovision with the elements brought by the Lusitanians of the Latin tradition of writing and linear time. Regarding the project and challenges of a new postcolonial society, the most controversial issues are addressed, such as feminism, formal education and the relationship between the elements of traditional and modern exotic, as well as the internal contradictions of struggle and policy As a conclusion, Pepetela makes an assessment of the period of the war and the rise to power of his political party, in the 1990s, with the disintegration of the Soviet republics and the fall of the Berlin Wall. According to the author, the collective utopia of a strong and just Angola ceases to exist to signify an individual ideology of their convictions regarding their political-ideological fidelity, since the contradictions that existed in the country as a colony were not overcome after their release. Nowadays, the mission of the intellectual subject is no longer to organize groups to take up arms, but to act in a classroom, in the role of teacher, in order to discuss the new challenges faced by Angolan society. Research Line in the Postgraduate Program in History: Frontier, politics and society. This dissertation did not receive any scholarship financial help or the like by the postgraduate program or other institutions of any kind.